Acting up : free speech, pragmatism, and American performance in the late 20th century - Nunns, Stephen (Recht und Gesellschaft., 2011)
Nunns examines how free speech became a centerpiece of American identity during the 20th century and how ideas of freedom of expression came to a head during the?Culture Wars? in the 1980s and?90s. He explores four case histories: performance artist Karen Finley and her court case revolving around public funding for the arts; the lawsuits involving the film I am Curious (Yellow); the controversy surrounding a community?s performance of Angels in America; and the racist songwriting of David Allen Coe.